A Brief Review of the European Directive on 3Rs and Facilitating Animal Experimentationon Ease: Review - Ali, Omeralfaroug (Acta Agraria Kaposváriensis, 2023)
The value of animals to humankind extends beyond their provision of food and physical resources; they also serve a wide range of purposes, including their role in experimentation. Given that animals play a substantial part in experimentation, it becomes imperative to improve their living conditions, at the very least as a form of compensation. As a result, the driving force behind the enactment of various legislations, including the European Union Directive (2010/63/EU), is human morality. This directive primarily pertains to specific European member states and is fundamentally aimed at safeguarding the welfare of animals used in experimentation by advocating for the implementation of the 3Rs: replacement, reduction, and refinement. Nevertheless, concerns have arisen, particularly regarding how the provisions of the directive might constrain or influence the advancement of experimentation, notably within the biomedical field. This review explores the nexus between Directive 2010/63/EU and the facilitation of animal experimentation, with a specific focus on the 3Rs. Findings reveal that the judicious application of the 3Rs markedly enhances the progress of experimentation without compromising the quality of outcomes. Furthermore, recent studies propose that the 3Rs alone may not suffice, suggesting the need to introduce additional relevant Rs. Hence, the current decrees are deemed adequate for a certain period, with potential modifications in the future. In order to encourage the advancement of experimentation without jeopardizing animal welfare, it is imperative to conduct periodic, routine reviews.
Keywords: animal welfare; reduction; refinement; replacement; research